Sorafenib combined with tarexib for first-line treatment of unresectable hepatocellular carcinoma and its predictive role and correlation with PD-L1 CTCs - Xu, Lin; Che, Xu (Frontiers in Oncology, 2024)
BackgroundThis study aims to evaluate the safety efficacy of combining the PD-1 antibody Tirelizumab with Sorafenib in the treatment of advanced hepatocellular carcinoma. Additionally we are committed to investigating the relationship between circulating tumor cell (CTC) counts/PD-L1 expression the prognosis of patients with advanced hepatocellular carcinoma.MethodsThis study included 32 patients with unresectable primary liver cancer who received treatment with Tislelizumab in combination with Sorafenib. Tislelizumab was administered via intravenous injection at a dose of 200 mg every 3 weeks, while Sorafenib was given orally at a dose of 400 mg twice daily. Patients were evaluated every 3 cycles (9 weeks) to assess the safety and efficacy of the treatment regimen. Prior to enrollment, all patients underwent CTC counting and assessment of PD-L1 expression in circulating tumor cells. The primary endpoint was the objective response rate (ORR), evaluated by the investigator according to the RECIST v1.1 criteria. Secondary endpoints aimed to assess the relationship between circulating tumor cell (CTC) counts or programmed death ligand 1 (PD-L1) expression and the prognosis of patients with advanced hepatocellular carcinoma.ResultsAs of November 2022, a total of 32 patients have been enrolled in the study and received combination treatment. Among the 32 patients, 31 (96.8%) tested positive for circulating tumor cells (CTCs), with counts ranging from 1 to 45 and a median of 7 (3, 11). PD-L1-positive CTCs were detected in 25 patients (78.1%). All 32 patients were followed up for 2 to 14 months, with a median follow-up time of 6 months. Correlation analysis revealed that distant metastasis, vascular invasion, and the presence of more than 5 CTCs were significantly associated with PD-L1-positive CTCs. The one-year overall survival rates for patients with PD-L1-positive CTCs and those with PD-L1-negative CTCs were 78.5% vs 64.3% (P = 0.309). Additionally, the one-year overall survival rates for the group with rising CTC counts compared to the group with stable or declining counts were 34.3% vs 90% (P = 0.063).ConclusionThe combination of Tislelizumab and Sorafenib demonstrates promising antitumor activity in the first-line treatment of hepatocellular carcinoma, with a relatively high objective response rate (ORR) and acceptable safety profile. Baseline CTC PD-L1 positivity can serve as a predictive marker for selecting hepatocellular carcinoma patients for PD-1/PD-L1 blockade therapy, and dynamic measurement of CTC changes can be used to monitor treatment efficacy.